2009
DOI: 10.1371/journal.pone.0004759
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst Injection of Wild Type Embryonic Stem Cells Induces Global Corrections in Mdx Mice

Abstract: Duchenne muscular dystrophy (DMD) is an incurable neuromuscular degenerative disease, caused by a mutation in the dystrophin gene. Mdx mice recapitulate DMD features. Here we show that injection of wild-type (WT) embryonic stem cells (ESCs) into mdx blastocysts produces mice with improved pathology and function. A small fraction of WT ESCs incorporates into the mdx mouse nonuniformly to upregulate protein levels of dystrophin in the skeletal muscle. The chimeric muscle shows reduced regeneration and restores d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…In our previous models with mdx mice, there was a noticeable lack of uniformity of dystrophin-positive fibers within the rescued muscle (Stillwell et al, 2009;Beck et al, 2011). However, in WT/SGd chimeras, dystrophin was detected in all fibers, but its overall staining intensity appeared to vary (Fig.…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…In our previous models with mdx mice, there was a noticeable lack of uniformity of dystrophin-positive fibers within the rescued muscle (Stillwell et al, 2009;Beck et al, 2011). However, in WT/SGd chimeras, dystrophin was detected in all fibers, but its overall staining intensity appeared to vary (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…However, in previous reports, we showed that it takes approximately10-30% ESC (or iPSC) incorporation to rescue mdx mice, which are predisposed to DMD (Stillwell et al, 2009;Beck et al, 2011). This disparity could be because of several factors linked to differences between the mdx and SGd-KO MD mouse models and/or with their respective interactions with the ESCs.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations